2016
DOI: 10.1017/s0033291716001392
|View full text |Cite
|
Sign up to set email alerts
|

The role of rumination in illness trajectories in youth: linking trans-diagnostic processes with clinical staging models

Abstract: Research in developmental psychopathology and clinical staging models has increasingly sought to identify transdiagnostic biomarkers or neurocognitive deficits that may play a role in the onset and trajectory of mental disorders and could represent modifiable treatment targets. Less attention has been directed at the potential role of cognitiveemotional regulation processes such as ruminative response style. Maladaptive rumination (toxic brooding) is a known mediator of the association between gender and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 212 publications
(231 reference statements)
0
43
0
Order By: Relevance
“…Past interventions have also shown promise to alter and improve perceived distress in diverse people with Type 2 diabetes [24] and Type 1 diabetes [25]. In chronic illness samples, negative cognitive emotion strategies have been linked to increases in distress and depressive symptoms [26], with rumination specifically associated with increases in emotional distress and depression, as well as dysregulation of the hypothalamic-pituitary-adrenal axis, which may represent a biological mechanism underlying relationships to poor health outcomes [9,27]. Our study further underscores the importance of negative cognitive emotion regulation and negative self-compassion as potential intervention targets to ameliorate diabetes distress.…”
Section: Discussionmentioning
confidence: 99%
“…Past interventions have also shown promise to alter and improve perceived distress in diverse people with Type 2 diabetes [24] and Type 1 diabetes [25]. In chronic illness samples, negative cognitive emotion strategies have been linked to increases in distress and depressive symptoms [26], with rumination specifically associated with increases in emotional distress and depression, as well as dysregulation of the hypothalamic-pituitary-adrenal axis, which may represent a biological mechanism underlying relationships to poor health outcomes [9,27]. Our study further underscores the importance of negative cognitive emotion regulation and negative self-compassion as potential intervention targets to ameliorate diabetes distress.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, one study found attenuated connectivity within the CCN among adolescent girls at high risk due to having a parental history of depression, although this study did not evaluate cognitive vulnerability features (Clasen et al, 2014). Given that aberrant CCN functioning may underlie cognitive factors that are known to confer risk for MDD onset or relapse (e.g., Abela and Hankin, 2011;Alloy et al, 2006;Langenecker et al, 2007aLangenecker et al, , 2014Stange et al, 2014Stange et al, , 2016; for a review, see Alloy et al, 2016), longitudinal clinical staging studies are needed to determine whether deficits in CCN connectivity confer similar risk, may represent an early scar of illness, or a combination thereof (Grierson et al, 2016;Peters et al, 2015). To this end, recent studies have demonstrated that greater CCN task-based activation (including dorsolateral prefrontal cortex and inferior parietal lobule) during inhibitory control predicted a greater likelihood of responding to antidepressant treatment for MDD (Gyurak et al, 2016;Langenecker et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Taken as a whole, many researchers have suggested the need for further revisions to interventions for BD-ASUD (Power, Nishimi, & Kizer, 2005;El-Guebaly, 2012;Kallestad et al, 2016), and that some evidence for additional adaptations may come to light from a greater understanding of the underlying shared risk factors for persistence of ASUD and BD (Grierson, Hickie, Naismith, & Scott, 2016). For example, functioning and quality of life in both BD and ASUD can be impaired by residual mood, anxiety and sleep symptoms (Judd et al, 2003;Gerra et al, 2014;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms can be partially ameliorated by pharmacotherapy, but it is increasingly clear that psychological interventions, especially cognitive, behavioural or self-regulation approaches, may be more efficient (McMurrich et al, 2012;Naqvi et al, 2015;Strickland, Reynolds, & Stoops, 2016). Also, symptoms of BD and ASUD may all be precipitated or maintained by dysfunctional cognitive emotional regulation (CER), particularly a negative ruminative response style (Gruber et al, 2011;Caselli et al, 2013;de Silveira & Kauer-Sant'Anna, 2015;Grierson et al, 2016). The exacerbation of mood disorder or ASUD may be, in part, driven by negative rumination.…”
Section: Introductionmentioning
confidence: 99%